Stage migration and survival outcomes in patients with cervical cancer at Stage IIIC according to the 2018 FIGO staging system: a systematic review and meta-analysis - Han, Ling; Chen, Yali; Zheng, Ai; Tan, Xin (Frontiers in Oncology, 2024)
ObjectiveTo summarize stage migration and survival outcomes in patients with cervical cancer at Stage IIIC according to the 2018 FIGO staging system, and to investigate prognostic factors influencing Stage IIIC1.MethodsPubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), International Clinical Trials Registry Platform (ICTRP), and Clinical Trials.gov were searched from inception to February 6, 2024. The analysis was conducted using STATA 16.0.ResultsA total of 25 studies with 82954 cervical cancer patients were included in the analysis. The migration rates to FIGO 2018 Stage IIIC ranged from 18% to 37% for early-stage tumors (Stage IB to IIA) in FIGO 2009, and from 32% to 52% for advanced stage tumors (Stage IIB to IIIB). The overall survival (OS) for Stage IIIC1 is poorer compared to Stage IB1 (HR 0.53, 95% CI 0.35-0.80, p=0.003) and Stage IB2 (HR 0.61, 95% CI 0.43-0.85, p=0.004). It is comparable to Stage IB3, yet it shows better survival outcomes than Stages IIB (HR 2.91, 95% CI 1.01-8.39, p=0.047), IIIA (HR 1.96, 95% CI 1.78-2.17, p=0.000), and IIIB (HR 1.56, 95% CI 1.04-2.35, p=0.031). Tumors size ≥4cm (HR 1.45, 95% CI 1.10-1.92, p=0.00), metastatic lymph node ≥ 3 (HR 2.21, 95% CI 1.56-3.15, p=0.000) and T stage are prognostic factors for OS of Stage IIIC1.ConclusionsThe migration rates to FIGO 2018 Stage IIIC varied between 18% and 52% for patients initially classified under FIGO 2009 Stages IB1 to IIIB. The FIGO 2018 staging system underscores the pivotal role of lymph node metastasis in predicting prognosis and provides valuable insights into the distinct prognostic implications associated with different stages, particularly for early stages. For advanced stages, incorporation of tumor-related factors such as T stage might better elucidate survival differences and guide clinical treatment decisions.Protocol registrationCRD 42023451793.